Comparison of chromohysteroscopy findings with histopathological findings in abnormal uterine bleeding - Kaur, Amanpreet; Bedi, Mini; Singh, Parvinder; Lamba, Pulkita; Kaur, Harbhajan; Suri, Vijay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Aim was to compare histological diagnosis of differently stained endometrial tissue on chromohysteroscopy. Methods: A total of 80 patients diagnosed with AUB and satisfying the study design were included in the study. Hysteroscopy followed by chromohysteroscopy was done using 1% methylene blue. Staining patterns were observed and guided biopsies were taken from differently stained areas and sent for histopathology. Results: On chromohysteroscopy, out of the 80 participants, 53 (66.3%) had focal staining and 27 (33.7%) had diffuse staining. The overall sensitivity, specificity, PPV and NPV of TVS in diagnosing uterine abnormalities was 51.7%, 45.1%, 34.9%, 62.2% respectively. The overall sensitivity, specificity, PPV and NPV for hysteroscopy were 96.6%, 41.2%, 48.3%, 95.5% respectively. The indices for chromohysteroscopy were as follows: sensitivity-69% for focal and 31% for diffuse staining, specificity-49.0% for focal staining and 69.7% for diffuse staining, PPV-43.5% for focal and 33.3% for diffuse staining, NPV-73.5% for focal staining and 62.3% for diffuse staining. Conclusions: The idea of staining of endometrium and taking a guided biopsy is exciting and is undoubtedly, better than a blind sampling. However, subjecting all the patient of AUB to chromohysteroscopy in order to find a major histopathological difference is questionable and needs larger trials to reach to concrete decision.